Cervical lymph node carcinoma metastasis from unknown primary site: a retrospective analysis of 154 patients. (2nd April 2018) - Wang, Yan; He, Sha‐Sha; Bao, Yong; Cai, Xiu‐Yu; Chen, Hai‐Yang; Yang, Xing‐Li; Chen, Dan‐Ming; Lu, Li‐Xia; Chen, Yong
Abstract: Despite advances in diagnosis and treatment, the existence of cervical lymph node carcinoma of unknown primary site (CCUP) has always been an urgent problem worldwide. There is still no consensus on the optimal management for CCUP. In this retrospective review, we analyze the clinical characteristics of CCUP patients treated at our institution and examine how these characteristics and treatments were associated with survival. Clinicopathologic features, treatments, and survival outcomes of 154 CCUP patients were collected from the hospital records and analyzed. Survival was estimated by Kaplan–Meier methods and compared by the log‐rank test. Cox proportional hazards regression analysis was used to assess the factors independently associated with overall survival (OS) and progression‐free survival (PFS). Median follow‐up period was 26.44 months (range, 0.53–146.53 months). Multivariate analysis showed N stage, pathologic type, and lymph node extranodal extension (ENE) to be independent prognostic factors for OS in CCUP patients, but not PFS. Subgroup analysis of patients who received radiotherapy showed that radiotherapy to the pharyngeal mucosa was associated with better OS ( P  =   0.045), but not with better PFS. Advanced N stage, nonsquamous cell carcinoma, and lymph node ENE predict poor prognosis in patients with CCUP. In addition, radiotherapy to suspicious mucosa is accompanied by better OS. These study findings should be useful to clinicians when selecting the treatment approach. Abstract : The optimal management approach for CCUP is still undecided, primarily because there are wide variations in disease characteristics between patients. This retrospective review attempted to identify the characteristics associated with overall survival and progression‐free survival. The findings show that advanced N stage, nonsquamous cell carcinoma pathology, and lymph node extracapsular extension are predictive of poor prognosis. Radiotherapy to the pharyngeal mucosa is associated with better overall survival, but not progression‐free survival.